Treatment Modalities for Trigeminal Neuralgia and the Need for Vigilance in Monitoring Adverse Drug Events: A Case Report - Addanki, Raja Narendra D.; Mannava, Anjali Srikanth; Velmurugan, Hemasri; Thangaraju, Pugazhenthan (Current Drug Safety, 2024)
Introduction: Trigeminal neuralgia is a rare condition characterised by paroxysms of intense pain in the distribution of the trigeminal nerve. This condition significantly diminishes the patient's quality of life, and the side effects from chronic use of medications for symptomatic relief further exacerbate their distress. Case Description: The case report discusses a patient diagnosed with Trigeminal Neuralgia who commenced carbamazepine treatment. The report tracks the disease's progression, medication adjustments, and the eventual emergence of vertigo due to long-term carbamazepine use. Conclusion: The article covers fundamental information about trigeminal neuralgia and its management and also offers a comprehensive review of the basics of vertigo. It delves into carbamazepine's mechanism of action and its associated side effects. The paper also looks at prospective therapy changes that could improve patients' quality of life.
Keywords: trigeminal neuralgia